Evidence for light-by-light scattering and searches for axion-like particles in ultraperipheral PbPb collisions at root s(NN)=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
Evidence for the light-by-light scattering process, γγ → γγ , in ultraperipheral PbPb collisions at a centre-of-mass energy per nucleon pair of 5.02 TeV is reported. The analysis is conducted using a data sample corresponding to an integrated luminosity of 390 μb−1 recorded by the CMS experiment at the LHC. Light-by-light scattering processes are selected in events with two photons exclusively produced, each with transverse energy Eγ T > 2 GeV, pseudorapidity |ηγ | < 2.4, diphoton invariant mass mγγ > 5 GeV, diphoton transverse momentum pγγ T < 1 GeV, and diphoton acoplanarity below 0.01. After all selection criteria are applied, 14 events are observed, compared to expectations of 9.0 ± 0.9 (theo) events for the signal and 4.0 ± 1.2 (stat) for the background processes. The excess observed in data relative to the background-only expectation corresponds to a significance of 3.7 standard deviations, and has properties consistent with those expected for the light-by-light scattering signal. The measured fiducial light-by-light scattering cross section, σfid(γγ → γγ ) = 120±46 (stat)±28 (syst)±12 (theo) nb, is consistent with the standard model prediction. The mγγ distribution is used to set new exclusion limits on the production of pseudoscalar axion-like particles, via the γγ → a → γγ process, in the mass range ma = 5–90 GeV.